Entrance, New Custom House - Ghosh, Ayan (2023)
New Custom House is entered through a semicircular arch with rusticated masonry, which contrasts with the upper levels which use regular ashlar masonry (dressed). Rustication is the deliberate use of rough or patterned surfaces, a technique extensively used by architects during the Edwardian era (1901-1910) and features in many buildings in Ballard Estate.